KOSMOLOGIS MASYARAKAT HINDU DI KAWASAN TRI DANU DALAM PELESTARIAN LINGKUNGAN HIDUP - Ida Bagus Gede Candrawan (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2015)
This article concerns the cosmological view of the Hindus around the area of tri danu in preserving their beautiful environment. Various means have been conducted by the tri danu community in which many parties, as the government as well as the tourism actors, have taken participations. Obviously even though now the condition has been in dilemma due to some obstacles, the cosmological understanding is still obeyed firmly by the Hindu community since they still believe in inherited mythologies.If the cosmology is not implemented hence there be various threats to come to endanger the environment, the human life as well.